Digital Financial Readiness and Sustainable Economic Resilience of MSMEs: The Mediating Role of Islamic Sustainable Business Practices (ISBP) in Medan City - Salman Munthe; Anggi Pratiwi Sitorus; Shintami Oktavia; Loranty Folia Simanjuntak (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Digital financial capability has become increasingly vital for the sustainability of micro, small, and medium enterprises (MSMEs). However, the contribution of this capability to resilience may depend on the governance and utilization of digital resources. This study investigates the impact of Digital Financial Readiness (DFR) on Sustainable Economic Resilience (SER), both directly and indirectly through Islamic Sustainable Business Practices (ISBP), among MSMEs in Medan City. A quantitative survey was conducted involving 320 MSME owners and managers selected through purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with 5,000 bootstrap subsamples. The results indicate that DFR positively influences ISBP (β = 0.612, p < 0.001) and SER (β = 0.287, p < 0.001), while ISBP also has a positive effect on SER (β = 0.498, p < 0.001). Furthermore, ISBP significantly mediates the relationship between DFR and SER (indirect effect β = 0.305, p < 0.001), suggesting partial mediation. The model accounts for 59.6% of the variance in SER and demonstrates predictive relevance. These findings suggest that digital financial readiness enhances MSME resilience not only through improved financial and operational capabilities but also through Sharia-compliant, ethical, socially responsible, and environmentally sustainable business practices. The study offers context-specific implications for local government, financial institutions, and MSME development agencies in Medan City to integrate digital financial capacity building with Islamic sustainability-oriented business support.